PREVALENCE OF TOXOPLASMA ANTIBODIES AMONG HORSES IN IRAQ - A. Al-Izzi, S.; H. Al-Judi ‎, A.; S. Abdul Redha, G. (The Iraqi Journal of Veterinary Medicine, 1987)
Sers. from 525 Arabian horses were tested for the presence of antibodies to Toxoplasma gondii by the indirect haemagglutination test. Of these sera, 39(7.43%) were positive. Thirty eight (8.15%) of seropositive animals were horses of two to 13 years of age and only one of the yearlings (1.5 year old) was seropositive. Twenty six of males (6.57%) and 13 cf females (10.08%) were seropositive. There was no significant (P)0.05) difference in the prevalence of toxoplasmosis between males and females.